Remediation of Lead-Contaminated Water by Red Yeast and Different Types of Phosphate - Tian, Da; Cheng, Xiaohui; Wang, Liyan; Hu, Jun; Zhou, Ningning; Xia, Jingjing; Xu, Meiyue; Zhang, Liangliang; Gao, Hongjian; Ye, Xinxin; Zhang, Chaochun (Frontiers in Bioengineering and Biotechnology, 2022)
Rhodotorulamucilaginosa (Rho) can secrete large amounts of extracellular polymeric substances (EPS) to resist lead (Pb) toxicity. Phosphate is an effective material for the remediation of Pb. This study explored the Pb remediation by the combination of Rho and different types of phosphate in water. To do so, four phosphates, namely, ferric phosphate (FePO4, Fe-P), aluminum phosphate (AlPO4, Al-P), calcium phosphate [Ca3(PO4)2, Ca-P], and phosphogypsum (PG) were employed along with Rho. Compared with Rho application, the addition of phosphate significantly promoted the secretion of EPS by Rho (21–25 vs 16 mg). The formed EPS-Pb contributes to the Pb immobilization in the combination of Rho and phosphate. After 6 days of incubation, Rho + phosphate treatments immobilized over 98% of Pb cations, which is significantly higher than Rho treatment (94%). Of all Rho + phosphate treatments, Ca-P and PG-amended Rho had higher secretion of EPS, resulting in higher Pb removal. Nevertheless, PG had the highest efficiency for Pb removal compared with other phosphates, which reached 99.9% after 6 days of incubation. Likewise, new Pb minerals, such as pyromorphite and lead sulfate, only appeared in Rho + PG treatment. Altogether, this study concludes on the combined application of Rho and phosphate as an efficient approach to promote Pb remediation, particularly using PG waste.